Bottle-Feeding Your Baby - Sarah A. Schmidt; Karla P. Shelnutt; Gail P. Kauwell (EDIS)
Families choose to bottle-feed their babies for many reasons. While bottle-feeding is not difficult, you need to know several things to feed your baby safely and ensure that he or she receives the nutrition and bonding needed for proper growth and development. If you are considering bottle-feeding your baby or have decided that bottle-feeding is the best option for your situation, this publication will help you learn about bottle-feeding. This 5-page fact sheet was written by Sarah A. Schmidt, Karla P. Shelnutt, and Gail P. A. Kauwell, and published by the UF Department of Family Youth and Community Sciences, April 2013.